2013
DOI: 10.12943/anr.2013.00005
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of A Gibbs Energy Minimizer In A Fission-Product Release Computer Program

Abstract: Article InfoKeywords: Modelling of fission-product release from nuclear fuel; Gibbs energy minimization; Lanthanide release from urania fuel; Fission-product

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This improved database was later used in a prototypic version of SOURCE by Barber [84] via direct coupling between SOURCE and the commercial thermodynamic software CHEMAPP [19]. As a result of this improved representation of nuclear fuel thermodynamics, the fractional fission gas release predicted by SOURCE was in closer agreement to experimental measurements [84] compared to the previous thermodynamic assessment from Corse [85]. While reassuring, this is not surprising given the great improvements in the thermodynamic treatment of the fuel.…”
Section: Sourcementioning
confidence: 84%
See 4 more Smart Citations
“…This improved database was later used in a prototypic version of SOURCE by Barber [84] via direct coupling between SOURCE and the commercial thermodynamic software CHEMAPP [19]. As a result of this improved representation of nuclear fuel thermodynamics, the fractional fission gas release predicted by SOURCE was in closer agreement to experimental measurements [84] compared to the previous thermodynamic assessment from Corse [85]. While reassuring, this is not surprising given the great improvements in the thermodynamic treatment of the fuel.…”
Section: Sourcementioning
confidence: 84%
“…A common challenge experienced with coupling a nuclear fuel code with a thermodynamics code is the increase in computational expense, particularly when solved on a FEA mesh. This issue has not been reported in the open literature among Class II SA codes; in fact, Barber reported that the increased computational expense with coupling ChemApp with SOURCE was quite acceptable [84]. The reason why the computational increase with code coupling is more problematic with FEA codes is simply because of the very large number of thermodynamic calls associated with a large number of finite elements in space and steps in time.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
See 3 more Smart Citations